Green synthesis of copper oxide (CuO) nanoparticles using Anredera cordifolia leaf extract and their antioxidant activity - Munandar, Nurharis; Kasim, Syaharuddin; Arfah, Rugaiyah; Basir, Djabal Nur; Hala, Yusafir; Zakir, Muhammad; Natsir, Hasnah (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
Our present study describes the green synthesis of copper oxide nanoparticles (CuONPs) using a leaf extract from Anredera cordifolia (AC). The presence of flavonoids, saponins, and alkaloids in the plant extract was confirmed by phytochemical analysis, and these chemicals can be used as reducing, stabilizing, and capping agents. UV-Vis Spectrophotometry, XRD, FT-IR, and SEM-EDS were used to characterize the CuONPs. The UV-Vis spectroscopy of the biosynthesized CuONPs revealed an absorption peak at 325 nm. The XRD graph also revealed that the Debye-Scherrer formula observed an average crystalline size of around 43.47 nm. EDS analysis confirmed the composition and purity of CuONPs. The presence of functional groups -OH, C=O, and C-O triggers the synthesis of CuONPs, according to FT-IR analysis. Furthermore, the CuONPs antioxidant property inhibited free radicals as antioxidants with an IC50 value of 34.20 g/mL.